The production of a new discursive regime about slums in Rio de Janeiro and the many faces of community-based entrepreneurship - De Tommasi, Livia; Velazco, Dafne (Revista do Instituto de Estudos Brasileiros, 2013)
This text is the result of an ethnographic research conducted in Cidade de Deus, one of the first territories in the city of Rio de Janeiro where the slum (favela) “pacification” program (UPP) promoted by the state government was installed. We tried to understand the transformations that happened after the beginning of the UPP program, analyzing the intervention apparatus triggered by public and private sectors, and their relationship with local grassrootsorganizations, and also with local dwellers. The research aims to show how the interventions manage to support the “pacification” and “integration” picture, at the same time that the apparatus that causes the expansion of domestic consumer market and the promotion of different forms of “grassroots entrepreneurship” is activated.